Essential Oils of Aromatic Plants with Antibacterial, Anti-Biofilm and Anti-Quorum Sensing Activities against Pathogenic Bacteria - Marlon Cáceres; William Hidalgo; Elena Stashenko; Rodrigo Torres; Claudia Ortiz (MDPI AG, 2020)
Both the ability of bacteria to form biofilms and communicate through quorum sensing allows them to develop different survival or virulence traits that lead to increased bacterial resistance against conventional antibiotic therapy. Here, seventeen essential oils (EOs) were investigated for the antimicrobial, antibiofilm, and anti-quorum sensing activities on Escherichia. coli O157:H7, Escherichia coli O33, and Staphylococcus epidermidis ATCC 12228. All essential oils were isolated from plant material by using hydrodistillation and analyzed by GC-MS. The antimicrobial activity was performed by using the microdilution technique. Subinhibitory concentrations of each EO were assayed for biofilm inhibition in both bacterial strains. Quantification of violacein in Chromobacterium violaceum CV026 was performed for the anti-quorum sensing activity. The cytotoxicity activity of the EOs was evaluated on Vero cell line by using MTT method. Thymol-carvacrol-chemotype (I and II) oils from Lippia origanoides and Thymus vulgaris oil exhibited the higher antimicrobial activity with MIC values of 0.37-0.75 mg/mL. In addition, these EOs strongly inhibited the biofilm formation and violacein (QS) production in a concentration-dependent manner, highlighting thymol-carvacrol-chemotype (II) oil as the best candidate for further studies in antibiotic design and development against bacterial resistance.